Analisis Butir Soal Pilihan Ganda Penilaian Akhir Semester pada Pembelajaran Tema 8 Praja Muda Karana Kelas III - Denna Delawanti; Yulianti Yulianti; Wildan Fajar Firdaus (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
Evaluation is often carried out after learning activities to assess the extent to which learning objectives have been achieved. The purpose of item analysis is to identify which questions are good, not so good, and which are bad. This research was carried out with the aim of analyzing multiple choice questions for the final semester assessment in learning theme 8 class III. This type of research is descriptive quantitative research. Sampling used a simple random sampling technique. The data collected was in the form of a final semester assessment of theme 8 learning for class III students at SDN 01 Putat Kidul, Malang Regency, totaling 12 students. Based on the results of the analysis of multiple choice questions in the Final Semester Assessment, it has been shown that: Theme 8 questions have a validity index with a "valid" category of 22 questions and an "invalid" category of 8 questions. (2) The questions in theme 8 have a high reliability index, namely 1. This shows that the questions can measure consistently, which is what is called reliable. (3) Theme 8 has 17 questions that are classified as difficult and 13 questions that are classified as very easy. From the research results, information was obtained, namely questions on theme 8 with a "difficult" category of 60% (17 items), and a "very easy" category of 40% (13 items). (4) The differentiating power of Final Semester Assessment questions on theme 8 with the "very good" category is 15% (4 items), the "good" category is 20% (6 items), the "revised" category is 10% (3 items), the “replaced” by 55% (17 items). (5) The effectiveness of the End of Semester Assessment distractors on questions in theme 8 with the "very good" category at 30% (9 items), the "good" category at 60% (18 items), the "Not good" category at 7% (2 items ), the “bad” category is 3% (1 item). The conclusion of this research is that the questions are of good quality and the questions in theme 8 have a high or reliable reliability index.